Effect of Sodium Metabisulphite Soaking and Types of Starter on Physicochemical Character of Modified Breadfruit Flour - Dian Histifarina; Adetiya Rachman (Jurnal Penelitian Pascapanen Pertanian, 2016)
Breadfruit flour is largely determined by the treatment during processing. Breadfruit contains quite high phenolic substances, so it can turn brown when it contacts with air. Moreover, the flour from alternatives food sources including breadfruit generally has more inferior in functional quality compare to wheat flour. Chemical modification with sodium metabisulphite and biological modification by fermentation can be done to improve the quality of breadfruit flour. The research objective was to determine the effect of concentration of sodium metabisulphite and types of starters on the characteristics of modified breadfruit flour. The research started from April 2013 to September 2013 at the Laboratory of Mechanization and Agricultural Technology (MTHP) Assessment Institute for Agricultural Technology (AIAT) West Java and Processing Laboratory of Pasundan University Bandung, using Factorial Completely Randomized Design 2 factors (3 types of starter and 2 soaking treatment), repeated 3 times. The parameters observed were physical properties (yield and whiteness), chemical properties (moisture content, ash content, and protein content), and functional properties (amylography). The results showed that the modified breadfruit flour produced has a yield ranging from 7.22 to 30.64% and moisture contents of 2.57 to 7.05%; Fermentation treatment with Bimo-CF starter and sodium metabisulphite produced the best physicochemical properties of breadfruit flour (moisture content 4.47%, ash content 2.28%, protein content 3.91%, and whiteness 77.13%). PENGARUH PERENDAMAN NATRIUM METABISULFIT DAN JENIS STARTER TERHADAP KARAKTER FISIKOKIMIA TEPUNG SUKUN TERMODIFIKASIPengolahan sukun menjadi tepung sukun sangat ditentukan oleh tahapan proses pengolahannya. Sukun mengandung zat fenolik cukup tinggi, sehingga apabila sudah kontak dengan udara dapat berubah menjadi coklat. Selain itu, tepung dari bahan pangan alternatif termasuk sukun umumnya memiliki mutu fungsional dibawah tepung terigu. Modifikasi proses pengolahan secara kimia dengan sodium metabisulfit (SMS) maupun secara biologis melalui fermentasi dapat dilakukan untuk memperbaiki dan meningkatkan mutu tepung sukun. Tujuan penelitian adalah untuk mengetahui pengaruh penggunaan bahan perendam dan jenis starter terhadap karakteristik tepung sukun termodifikasi. Rancangan yang digunakan adalah RALF (Rancangan Acak Lengkap Faktorial) dengan 2 faktor (jenis starter 3 taraf dan perendaman 3 taraf), diulang 3 kali. Parameter yang diamati meliputi sifat fisik (rendemen dan derajat putih), sifat kimia (kadar air, kadar abu, dan kadar protein), dan sifat fungsional (amilograf). Hasil penelitian menunjukkan bahwa tepung sukun termodifikasi yang dihasilkan memiliki rendemen berkisar antar 7,22 – 30,64% pada kadar air 2,57-7,05%; Perlakuan perendaman dalam sodium metabisulfit (SMS) dan fermentasi dengan starter bimo-CF menghasilkan sifat fisiko kimia tepung sukun terbaik (kadar air 4,47%, kadar abu 2,28% kadar protein 3,91 dan derajat putih 77,13%).